1995
DOI: 10.4037/ajcc1995.4.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation and hemodynamic response in critically ill, mechanically ventilated adults during intrahospital transport

Abstract: BACKGROUND: Despite the frequency of intrahospital transport of critically ill patients, little research has been done on this topic and the findings are contradictory. OBJECTIVES: To describe arterial oxygen saturation by pulse oximetry, heart rate, heart rhythm, and systolic blood pressure and equipment problems in critically ill, mechanically ventilated adults during intrahospital transport. METHODS: The sample consisted of 36 critically ill, mechanically ventilated adults who required transport out of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…The inverse relationship between physician experience and UE/SUE rates is consistent with Evans and Winslow. 16 However, we are unable to determine the reasons for this relationship. It may relate to the quality of care provided, reporting bias, or confounders (e.g., patient selection).…”
Section: Discussionmentioning
confidence: 91%
“…The inverse relationship between physician experience and UE/SUE rates is consistent with Evans and Winslow. 16 However, we are unable to determine the reasons for this relationship. It may relate to the quality of care provided, reporting bias, or confounders (e.g., patient selection).…”
Section: Discussionmentioning
confidence: 91%
“…Changes in¯ow of vasoactive drugs may contribute to the haemodynamic instability often seen when moving intensive care patients. 7 Relevant time without infusion was found up to infusion rates of >5 ml h ±1 . The greater compliance of the Ivac 770 system in¯uenced the marked effect of changes in out¯ow pressure on this apparatus.…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of clinical complications in this study was elevated, similar to the report for interhospital transports of newborn infants published by Lim and Ratnavel (12) . Other studies have also reported elevated rates of clinical problems during intrahospital transports of adults and children, varying from six to 71% (1,2,13,15,(18)(19)(20) , indicating that the risk of morbidity in intrahospital transports may be comparable with the risk SNC: central nervous system; O 2 : oxygen; Hosmer-Lemeshow test: 0.633, p<0.001. MV: mechanical ventilation.…”
Section: Discussionmentioning
confidence: 93%